2013
DOI: 10.1073/pnas.1317019110
|View full text |Cite
|
Sign up to set email alerts
|

Network model of top-down influences on local gain and contextual interactions in visual cortex

Abstract: The visual system uses continuity as a cue for grouping oriented line segments that define object boundaries in complex visual scenes. Many studies support the idea that long-range intrinsic horizontal connections in early visual cortex contribute to this grouping. Top-down influences in primary visual cortex (V1) play an important role in the processes of contour integration and perceptual saliency, with contour-related responses being task dependent. This suggests an interaction between recurrent inputs to V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 60 publications
3
94
1
Order By: Relevance
“…S2). This result supports a neural network model involving gating of V1 lateral interactions through feedback modulation (11)(12)(13).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…S2). This result supports a neural network model involving gating of V1 lateral interactions through feedback modulation (11)(12)(13).…”
Section: Discussionsupporting
confidence: 85%
“…Although many lines of converging evidence suggest that V1 is intimately involved in contour integration, circuitbased models have to take into account the findings that contour grouping is more than a bottom-up or hard-wired process, but that it is strongly dependent on top-down feedback influences (5, 14-17). Surface segmentation, another important intermediate stage in processing of visual images, is also mediated by interactions between feedforward and feedback connections (18).We have proposed a model whereby cortical feedback contributes to the effective connectivity of horizontal connections within V1 (13,19). A possible role of higher cortical areas in this process is to disambiguate local image components by creating a template that is fed back to V1, which then can selectively enhance object components and suppress interfering background (20)(21)(22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to recognize, however, that changes in bottomup stimulus encoding do not explain all forms of PL (6,56,71,72). For example, Gilbert and colleagues found that while perceptual training on an embedded contour detection task has little effect on basic response properties of monkey V1 neurons, it has a pronounced effect on how V1 neurons are modulated by stimulus context (6,56,71).…”
Section: Significancementioning
confidence: 99%